Genetic variants in epithelial–mesenchymal transition genes as predictors of clinical outcomes in localized prostate cancer. (26th March 2020) - Deng, Yang; Xie, Kunlin; Logothetis, Christopher J; Thompson, Timothy C; Kim, Jeri; Huang, Maosheng; Chang, David W; Gu, Jian; Wu, Xifeng; Ye, Yuanqing
Abstract: Background: Epithelial–mesenchymal transition (EMT) plays a pivotal role in the progression of prostate cancer (PCa). However, little is known about genetic variants in the EMT pathway as predictors of aggressiveness, biochemical recurrence (BCR) and disease reclassification in localized PCa. Patients and methods: In this multistage study, we evaluated 5186 single nucleotide polymorphisms (SNPs) from 264 genes related to EMT pathway to identify SNPs associated with PCa aggressiveness and BCR in the MD Anderson PCa (MDA-PCa) patient cohort ( N = 1762), followed by assessment of the identified SNPs with disease reclassification in the active surveillance (AS) cohort ( N = 392). Results: In the MDA-PCa cohort, 312 SNPs were associated with high D'Amico risk ( P < 0.05), among which, 14 SNPs in 10 genes were linked to BCR risk. In the AS cohort, 2 of 14 identified SNPs (rs76779889 and rs7083961) in C-terminal Binding Proteins 2 gene were associated with reclassification risk. The associations of rs76779889 with different endpoints were: D'Amico high versus low, odds ratio [95% confidence interval (CI)] = 2.89 (1.32–6.34), P = 0.008; BCR, hazard ratio (HR) (95% CI) = 2.88 (1.42–5.85), P = 0.003; and reclassification, HR (95% CI) = 2.83 (1.40–5.74), P = 0.004. For rs7083961, the corresponding risk estimates were: D'Amico high versus low, odds ratio (95% CI) = 1.69 (1.12–2.57), P = 0.013; BCR, HR (95% CI) = 1.87 (1.15–3.02), P = 0.011 and reclassification, HR (95% CI) = 1.72 (1.09–2.72), P = 0.020. There were cumulative effects of these two SNPs on modulating these endpoints. Conclusion: Genetic variants in EMT pathway may influence the risks of localized PCa's aggressiveness, BCR and disease reclassification, suggesting their potential role in the assessment and management of localized PCa. Abstract : Two single nucleotide polymorphisms (rs76779889 and rs7083961) in C-terminal Binding Proteins 2 gene were associated with aggressiveness, biochemical recurrence and reclassification risk in localized prostate cancer. There were cumulative effects of these two SNPs on modulating these endpoints.